COASTAL EROSION AND FLOODING: CAUSES AND CONSEQUENCES - BABU, Dr. CH. ANIL; NARAYANA, Dr. P.SATYA (IJRDO-Journal of Applied Science, 2016)
Shoreline changes induced by erosion and accretion are natural processes that take place over a range of time scales. They may occur in response to smaller-scale (short-term) events, such as storms, regular wave action, tides and winds, or in response to large-scale (long-term) events such as glaciations or organic cycles that may significantly alter sea levels (rise/fall) and tectonic Activities that cause coastal land subsidence or emergence. Hence, most coastlines are naturally dynamic, and cycles of erosion are often an important feature of their ecological character. Wind, Waves and currents are natural forces that easily move the unconsolidated sand and soils in the Coastal area, resulting in rapid changes in the position of the shoreline along Andhra coast present we discuss about coastal erosion causes and consequences among Andhra coast fully depend upon on secondary data study.